The relationship between stress and physical activity among adolescent in UiTM Jengka, Pahang / Norfatihah Mohd Noor - Mohd Noor, Norfatihah (Faculty of Sport Science and Recreation, 2018)
Stress for adolescent was an important stressor before they enter the more challenging part in their lives. Besides, the difficulties in handling the stress will lead to the anxiety, depression and poor coping skills. Nevertheless, by engaging in a physical activity has proved to be one of the coping mechanism in handling the stress and any psychological problem. The purpose of this research was aimed to investigate the significant relationship between stress and physical activity among adolescent in UiTM Jengka. In this study, data were collected using a Perceived Stress Scale (PSS-I0 item) and Physical Activity Questionnaire for Adolescent (PAQ-A). The statistical sample was 140 adolescents with 70 male respondents and 70 female respondents that age 18 years old and 19 years old. In this study, the analysis used was the descriptive statistic, independent sample t-test, and Pearson correlation. Results showed no significant relationship between stress and physical activity among male and female adolescent. Moreover, results obtained showed that the mean value of stress for the male adolescent was 22.900 ± 5.36 whereby the mean value of stress for the female adolescent was 22.914 ± 4.58. In addition, the mean value of physical activity for the male adolescent was 2.00 ± .55 whereby for the female adolescent was 1.61 ± .42. Therefore, findings unveiled that there was no correlation between stress and physical activity among adolescent in UiTM Jengka and results encourage a search for further knowledge regarding the association between stress and the specific domain of physical activity.